Model Hybrid Filantropi: Integrasi Dana Sosial dan Kewirausahaan Sosial untuk Pemberdayaan Berbasis Data - A. Fahmi Zakariya; Ika Nazilatur Rosida (MONETARIUM: Journal of Economics Business and Management, 2025)
This research aims to conceptualize a hybrid philanthropy model that systematically integrates social funds and social entrepreneurship as a framework for advancing data driven community empowerment. Philanthropic practices in Indonesia have traditionally been dominated by charitable and consumptive approaches that yield limited and unsustainable social outcomes. In contrast, social entrepreneurship offers significant potential to address structural social challenges through innovative, market oriented mechanisms, yet its progress remains constrained by insufficient access to capital. This study employed a qualitative descriptive design with an exploratory case study approach. It investigated the practices of philanthropic institutions, social entrepreneurs, and beneficiary communities. Data were collected through in depth interviews, participant observation, document analysis, and an extensive literature review. The data were then analyzed using Miles and Huberman’s interactive model, which consisted of data reduction, data display, and conclusion drawing. The research showed that the success of integration is determined by the availability and quality of structured data systems. Disparities in data access and the weak evidence base are the main obstacles in planning and evaluating philanthropic programs. Through the hybrid philanthropy model, this study develops a framework connecting three key components: (1) social funding as a source of financial resources and legitimacy, (2) social entrepreneurship as a driver of empowerment through innovative business models, and (3) impact based data systems as the foundation for accountability, efficiency, and targeting accuracy. The integration of these components results in a social impact hierarchy that illustrates the logical flow from inputs, processes, to outcomes and long term impacts. The implementation of this model has the potential to shift the paradigm of philanthropy in Indonesia from charity based to investment based, while strengthening the social economic resilience of communities through an evidence based empowerment ecosystem.